Peran Gerakan Literasi Sekolah Untuk Menumbuhkan Pendidikan Karakter Siswa Di Sd - Syindi Syindi; Arna Juwairiyah; Erwin Eka Saputra (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The problem in this study is in strengthening character education through the school literacy movement currently used, namely character values through the school literacy movement are not optimal. The purpose of this study is to describe the implementation of the School Literacy Movement program developed at SD Negeri 09 Mawasangka Tengah to internalize character values in grade V students in the 2023/2024 Academic Year. This study uses a descriptive qualitative research method. The subjects of this study were Indonesian language teachers while the informants were Grade V teachers and students. Data collection techniques were carried out through interviews, observations and documentation. Data validity testing through source and method triangulation. While the analysis technique using an interactive analysis model includes: data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that strengthening character education through the implementation of the Grade V School Literacy Movement began with the School Literacy Movement program which was carried out in various stages including the preparation stage, implementation stage, and evaluation stage. In addition, there is also a special program from the School Literacy Movement which is divided into Daily Programs, Weekly Programs, Monthly Programs, Semester Programs and Annual Programs. The impact of the School Literacy Movement activities in strengthening character education is able to carry out regularly the existing rules, attitudes and behaviors that are obedient in carrying out the teachings of the religion they believe in, thinking and doing something to produce something new that has been owned, attitudes that show a sense of pleasure in talking to others, enjoying socializing, and working together with people and actions not to cause damage to the environment and to care for the environment well.